Women’s Motivation and Constributions in Digital Literacy Activities: A Lesson from Literary Work Appreciation - Aztry, Aisiyah; Damaianti, Vismaia S.; Mulyati, Yeti; Sastromiharjo, Andoyo (Universitas Pendidikan Mandalika, 2024)
This research aims to describe the contribution of women as digital literacy activists and the form of community activities. This research is a phenomenological research, which describes the phenomena that occur with a qualitative approach, descriptive analysis and data collection techniques of interviews, literature studies and documentation. The results of the study were obtained in the form of motivation, contribution and activity of women in digital literacy. Women's motivation is due to an internal drive in the form of self-actualization, values, awareness and empathy. The external impetus is due to the phenomenon of low interest in reading, the influence of social media and the urgency of community education. The form of contribution is in the form of commitment, time, material, ideas and innovation. Forms of digital literacy activities such as reading, writing, discussing and appreciating literary works with a series of activities arranged and agreed upon together and guided by contributors or collaborating with other parties. The implication of the results of this study is that it can be used as a consideration for stakeholders to give appreciation in the form of awards to women digital literacy activists. Providing legal assistance for the legality of digital literary literacy communities, as well as funds for activities and the creation of literary works. Another thing is as a basis for follow-up to hold certified and nationally recognized training or seminars.